Relationship between breastfeeding duration and the development of malocclusion and dental caries in children - Monika Żbikowska; Oskar Tokarczuk; Gabriela Durlej; Leszek Szalewski; Joanna Wysokińska-Miszczuk (Scientific Reports)
Abstract Breastfeeding plays a crucial role in the proper development of a child, providing numerous health benefits. This study aimed to investigate the relationship between breastfeeding habits and the development of disorders in the stomatognathic system, including malocclusions and dental caries. The research involved 109 children aged 6 months to 15 years. The study included an oral examination and a questionnaire completed by parents regarding breastfeeding duration, feeding practices, and the child’s oral hygiene habits. The results showed no significant correlation between breastfeeding or formula feeding and an increase in the child’s caries intensity index (dmft) (p < 0.05). However, formula feeding at night, particularly when the child fell asleep with a bottle, was associated with a higher risk of dental caries (η = 0.716). A strong relationship was observed between prolonged breastfeeding, especially when the child slept while breastfeeding, and the occurrence of malocclusions (η = 0.605). Children breastfed beyond 12 months or who continued to breastfeed during sleep were more likely to develop malocclusions, such as open bite or crossbite. The study emphasizes the importance of proper breastfeeding habits which may contribute to the development of malocclusion. While breastfeeding provides several health advantages, certain breastfeeding habits may contribute to the development of malocclusions, necessitating further research to determine the optimal duration and methods of breastfeeding to promote balanced oral development. Dental professionals in their dental practice should educate parents about proper nutrition and childcare from birth in order to eliminate habits that may negatively affect the oral health of their children.